Diversity of Ferns: Identification of Types Pteridophyta In Batang Gadis National Park, North Sumatera, Indonesia - Harahap, Lia Junita; Harahap, Idris; Febrianti, Rina; Teresa Hutagaol, Robiah (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The diversity of ferns is very high, especially in Indonesia. Ferns (Pteridophyta) are a division of the kingdom Plantae whose members have true roots, stems and leaves, as well as carrying vessels. Ferns (Pteridophyta) live in moist areas (hygrophytes) both epiphytes (attached to trees, wood, rocks) and terrestrial (soil). The diversity of ferns is related to altitude and other abiotic factors such as temperature, pH, humidity and light intensity. This research used qualitative methods through fern exploration activities in the Batang Gadis National Park, specifically at Sopo Tinjak Resort 6. The research results obtained 8 types of ferns in Resort 6 of the Batang Gadis Mandailing Natal National Park Area, North Sumatera, Indonesia.